Exploring The Cross Countries Endurance, Evidence of Indonesian and Malaysian Sharia Banks Financial Performance - Kurniawan, Muhammad; Normasyhuri, Khavid; Anggraeni, Erike (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 18 No 2 (2023), 2023)
The Islamic banking industry should be balanced with good financial performance to create stakeholders' trust in the funds they invest. This study examines financial performance by comparing the Islamic banking industry in Indonesia and Islamic banks in Malaysia during the Covid-19 pandemic using the MSI (Maqashid Sharia Index) and CAMELS (Capital, Asset, Management, Earning, Liquidity, Sensitivity of Market Risk) methods. The research adopts a quantitative design with a comparative approach. The implementation research period was in the era of covid-19 with the period 2020-2022. Sampling used purposive sampling at Indonesian Islamic Commercial Banks and Malaysian Islamic Commercial Banks with a total sample of 36. Hypothesis testing using the Independent T-Test. The results of the study provide the fact that the financial performance of the Islamic banking industry in Indonesia has good value and compliance compared to Islamic banks in Malaysia based on the MSI and CAMELS in the conditions of Covid-19. Keywords: islamic bank, financial performance, COVID-19